Pengaruh Pendekatan Contextual Teaching And Learning Terhadap Kemampuan Koneksi Matematis Siswa - Maria Indrawati Widonda; Bedilius Gunur; Yohanes Kurniawan (UNIKA SANTU PAULUS RUTENG, 2018)
The goal of this research is to know the students’ mathematical connection skill improves well by using contextual teaching and learning (CTL) than using conventional approach. This research is pseudo experiment, using research design posttest only control group design. The population in this research is 95 students from three different classes. The sampling technique used is random sampling, in which the equality test priorly applied. The data collection intrument is a test. Before analysing data, it is priorly conducted analysis prerequisite test, which is a homogeneity and normality test. The data is analysedusing . Based on the analysis, the result of this research is that is so is rejected and is accepted meaning the students’ mathematical connection skill improves well by using contextual teaching and learning (CTL) than using conventional approach.